2021
DOI: 10.1111/ijcp.14806
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal bleeding in patients 80 years old and over. A comparison with younger patients and risk factors analysis for in‐hospital and delayed mortality

Abstract: Introduction Outcomes in old patients with upper gastrointestinal bleeding (UGIB) have been scarcely studied. Our aim was to compare very old individuals (>80 years old) with younger patients with UGIB, and to identify risk factors for the main outcomes. Methods A single‐centre prospectively collected database was analysed. Descriptive, inferential and multivariate logistic regression models were performed. Main clinical outcomes were in‐hospital and delayed 6‐month mortality. Results 698 patients were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…In terms of prognosis and application of antithrombotic drugs (Table 2), we found that elderly patients had a longer hospital stay, a higher proportion of patients with a history of antiplatelet drugs, and a higher proportion of patients who used anticoagulants during hospitalization. The median time for elderly patients to use antiplatelet drugs after admission was 10 [4, 14] days, and the median time for using anticoagulant drugs was 6 [3,13] days. The median time for young patients to use antiplatelet drugs after admission was 8 [3,13] days, and the median time for using anticoagulant drugs was 8 [4,11] days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of prognosis and application of antithrombotic drugs (Table 2), we found that elderly patients had a longer hospital stay, a higher proportion of patients with a history of antiplatelet drugs, and a higher proportion of patients who used anticoagulants during hospitalization. The median time for elderly patients to use antiplatelet drugs after admission was 10 [4, 14] days, and the median time for using anticoagulant drugs was 6 [3,13] days. The median time for young patients to use antiplatelet drugs after admission was 8 [3,13] days, and the median time for using anticoagulant drugs was 8 [4,11] days.…”
Section: Resultsmentioning
confidence: 99%
“…The median time for elderly patients to use antiplatelet drugs after admission was 10 [4, 14] days, and the median time for using anticoagulant drugs was 6 [3,13] days. The median time for young patients to use antiplatelet drugs after admission was 8 [3,13] days, and the median time for using anticoagulant drugs was 8 [4,11] days. There was no statistical difference between the two groups in the time interval between the resumption of drug application.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have primarily relied on multivariable logistic regression to identify risk factors associated with outcomes in older populations with UGIB [ 17 ]. We employed a combination of traditional methods and innovative techniques, such as StepAIC, LASSO, ENT, RFE, and Best subset selection, to facilitate the selection of key variables during the training and prediction modeling process.…”
Section: Discussionmentioning
confidence: 99%
“…Higher creatinine levels are associated with higher patient frailty and complexity, although the correlation with creatinine level remains after adjusting for these factors in this study. However, creatinine is an important risk factor for gastrointestinal bleeding and has been associated with increased mortality in several studies [ 14 , 15 , 16 ]. For this reason, the emergency physicians and endoscopists could be more motivated to request and perform early EGDS in these patients.…”
Section: Discussionmentioning
confidence: 99%